2010
DOI: 10.1080/07315724.2010.10719829
|View full text |Cite
|
Sign up to set email alerts
|

Milk Enriched with Conjugated Linoleic Acid Fails to Alter Blood Lipids or Body Composition in Moderately Overweight, Borderline Hyperlipidemic Individuals

Abstract: Results from this study fail to support the role of milk enriched naturally with CLA containing c-9, t-11 or synthetically with c-9, t-11 and t-10, c-12 CLA isomers in modulation of lipid profiles or body composition in moderately overweight, borderline hyperlipidemic individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 30 publications
5
48
0
2
Order By: Relevance
“…The authors stated that this was important due to links between enzymic activity and the production of carcinogens. However, it is important to note that the main aim of the study was to examine the effects of CLA-enriched milk on lipid metabolism and body composition (38) . Currently the evidence for the anti-carcinogenic properties of CLA in human subjects is limited to observational studies, with broader epidemiological evidence not specifically focusing on CLA but rather on milk and dairy products.…”
Section: Methodsmentioning
confidence: 99%
“…The authors stated that this was important due to links between enzymic activity and the production of carcinogens. However, it is important to note that the main aim of the study was to examine the effects of CLA-enriched milk on lipid metabolism and body composition (38) . Currently the evidence for the anti-carcinogenic properties of CLA in human subjects is limited to observational studies, with broader epidemiological evidence not specifically focusing on CLA but rather on milk and dairy products.…”
Section: Methodsmentioning
confidence: 99%
“…Mean and standard deviation for TC, HDL-C, LDL-C and TAG before and after placebo or CLA consumption were extracted. Data from the following studies were not extracted: four studies without complete data for analysis (35)(36)(37)(38) , four studies without a placebo group (32,(39)(40)(41) , one study that considered special polymorphisms (PPARγ2, Pro12Ala) of healthy adults (42) , one study done on adolescents (43) and participants of three studies had signs of metabolic syndrome or borderline hyperlipidaemia (44)(45)(46) . Complete information about excluded studies is shown in Fig.…”
Section: Data Extractionmentioning
confidence: 99%
“…The ANSES opinion (2011) also identified three recent reports on the effects of CLA on blood lipids that had not been included in the meta-analyses quoted above (Joseph et al, 2011;Pfeuffer et al, 2011;Venkatramanan et al, 2010). Two of them had a cross-over design, included 15 (Venkatramanan et al, 2010) and 36 (Joseph et al, 2011) overweight subjects, respectively, and provided CLA (as the c-9,t-11 isomer or the 50:50 isomer mixture) at doses up to 2.8 g/day for 8 weeks.…”
Section: Effects On Blood Lipids and Lipoproteinsmentioning
confidence: 99%
“…Two of them had a cross-over design, included 15 (Venkatramanan et al, 2010) and 36 (Joseph et al, 2011) overweight subjects, respectively, and provided CLA (as the c-9,t-11 isomer or the 50:50 isomer mixture) at doses up to 2.8 g/day for 8 weeks. The third study had a parallel design, included about 20 overweight men per study arm, lasted 4 weeks and used the 1:1 CLA isomer mixture at a dose of 3.6 g/day (Pfeuffer et al, 2011).…”
Section: Effects On Blood Lipids and Lipoproteinsmentioning
confidence: 99%
See 1 more Smart Citation